Pengaruh Digitalisasi, Literasi Keuangan, dan Persepsi Risiko Terhadap Keputusan Investasi - Resyita, Cherina Pancha; Khoiriyah, Rahmawati (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2023)
This research aims to examine the influence of digitalization, financial literacy and risk perception on investment decision making. This research is a type of quantitative research that obtains primary data by distributing questionnaires. The population in this study were students from the Faculty of Economics and Islamic Business, Raden Mas Said State Islamic University, Surakarta who had made investment. The sample in this research was selected using a non-probability method in the form of a purposive sampling technique. The samples used in this study amounted to 100 samples.. Data analysis was carried out using multiple linear regression analysis supported by the IBM Statistics SPSS 23 program. The research results show that there is a significant influence.